(untitled) (PETITUM, 2024)
ABSTRACT: This research aims to analyze law application of withholding and withdrawing therapy for critical patients in Intensive Care Unit (ICU) as well legal liability consequences/impact caused. Research methods were normative-empirical. Research results: no regulations regarding criteria for terminal state and futile patients by the hospital, no team formed by Medical/Ethical Committee with authority to decide on delaying and stopping therapy, implementation of withholding and withdrawing therapy is in accordance with services grouping that can and cannot be carried out and informed consent has been carried out to provide verbal and written approval and rejection. This illustrates that Regulation of Indonesia Health Minister (Permenkes) number 37 of 2014 chapter 14 and 15 has not been fully implemented by hospitals and medical personnel, whereas Permenkes is legal protection that guarantees hospitals and medical personnel in carrying out withholding and withdrawing therapy because these regulations uncontradictory with criminal or civil law aspect. ABSTRAK: Penelitian ini bertujuan menganalisa penerapan hukum penundaan dan penghentian terapi terhadap pasien-pasien kritis di Intensive Care Unit (ICU) serta pertanggungjawaban akibat hukum/dampak yang ditimbulkannya. Penelitian menggunakan metode normatif-empiris. Hasil penelitian: belum ada regulasi terkait kriteria pasien terminal state dan futile oleh Rumah Sakit, belum ada tim dibentuk oleh Komite Medik/Etik berwenang memutuskan penundaan dan penghentian terapi, pelaksanaan tindakan penundaan dan penghentian terapi telah sesuai dengan pengelompokan pelayanan yang dapat dan tidak dapat dilakukan serta telah dilakukan informed consent tindakan persetujuan dan penolakan tindakan secara lisan dan tertulis. Hal menggambarkan Peraturan Menteri Kesehatan (Permenkes) Republik Indonesia nomor 37 tahun 2014 pasal 14 dan 15 belum sepenuhnya dijalankan oleh Rumah Sakit dan tenaga medis sedangkan Permenkes tersebut merupakan payung hukum yang menjamin Rumah Sakit dan tenaga medis dalam melakukan tindakan penundaan dan penghentian terapi pada pasien kritis yang dirawat di ICU karena peraturan tersebut tidak bertentangan dengan aspek hukum pidana maupun perdata.